Aspects Related to the Influence of Christianity on the Society - Mihai Handaric (Randwick International of Social Science Journal, 2021)
In this paper the author analyzes the influence of Christianity on society. There will be demonstrated that through its structure, man was created to live in the community. He discovers himself by relating to the world surrounding him, as it is argued by Martin Heidegger, and Martin Buber. Here we also include the relationship with the transcendent. The philosophical and sociological arguments help us understand the influence Christianity had on European society. The religion of the European nations had a strong influence on the civilization of the continent and the world. Researchers have come to the conclusion that man was created with an innate religious feeling. Rudolf Otto sought to demonstrate that man's religious experience can only be explained by the aprioric existence of the sacred. So did Mircea Eliade, who introduced a new term "hierophany" to define the act of experiencing the sacred. There were also researchers who reinterpreted the relationship with the sacred. Emile Durkheim argued that ultimately, religion in its present form will be replaced by a so-called "civic religion," which will replace religious services in churches. Accepting the perspective of Scripture, the author tries to show the idea of the presence of Divinity in the believer's life (John 14:15-26). Jurgen Moltman asserts that if society were to enter the process of Christ's discipleship, she would discover the divine alternatives that bring the long-awaited results. Max Weber argued that Christian religion, and especially the sects of Protestantism, had a decisive role in influencing the culture and civilization of modern Europe, and the world at large. From his point of view, the decision of man in capitalist society to make a great effort in his work, has a religious motivation, namely, the doctrine of predestination. Considering that the moral and theological dimension of Christianity lies at the root of human significance, Christians struggle to defend the revealed message. A good example is given by Francis Schaeffer, who in his book Trilogy pleads to preserve the traditional moral values of the Bible. Schaeffer attempts to link the idea of revelation, as it is presented in the Christian Bible, with the discovering of man's significance.